Effect of amino acid composition of elastin‐like polypeptide nanoparticles on nonspecific protein adsorption, macrophage cell viability and phagocytosis. Issue 12 (7th August 2021) - Bahniuk, Markian S.; Ortega, Van A.; Alshememry, Abdullah K.; Stafford, James L.; Goss, Greg G.; Unsworth, Larry D.
Abstract: Development of elastin‐like polypeptide (ELP) biomaterials is widespread, but information critical for clinical deployment is limited, with biocompatibility studies focused on a narrow cross‐section of ELP sequences. Macrophages can impair biomaterial systems by degrading or isolating the biomaterial and by activating additional immune functions. Their phagocytic response will reveal early immune biocompatibility of ELP nanoparticles (NPs). This study examines that response, induced by the adsorbed protein corona, as a function of ELP guest amino acid, chain length and NP diameter. The breadth of proteins adsorbed to ELP NPs varied, with valine‐containing ELP NPs adsorbing fewer types of proteins than leucine‐containing constructs. Particle diameter was also a factor, with smaller leucine‐containing ELP NPs adsorbing the broadest range of proteins. Macrophage viability was unaffected by the ELP NPs, and their phagocytic capabilities were unimpeded except when incubated with a 500 nm valine‐containing 40‐mer. This NP significantly decreased the phagocytic capacity of macrophages relative to the control and to a corresponding 500 nm leucine‐containing 40‐mer. NP size and the proportion of opsonin to dysopsonin proteins likely influenced this outcome. These results suggest that certain combinations of ELP sequence and particle size can result in an adsorbed protein corona, which may hinder macrophage function. Abstract :